Sustainability at Home: The Development of an Efficient Framework for Home Energy-Saving Applications - Sarunporn Tongsubanan; Kittichai Kasemsarn (Designs, 2023)
Energy consumption is increasing due to the rise in the world population, industrialization, and urbanization, particularly in the residential sector, attributed to a lack of user-friendly tools. This study seeks to create a research framework and wireframe for home energy-saving applications. A systematic literature review (SLR) was conducted using the VOSviewer software version 1.6.18 tool to pinpoint the research problems. Three key research problems were identified: Inadequate information presentation for both experts and non-experts, insufficient consideration for middle-aged and elderly users, and difficulties in interpreting graphics or images on the application’s display screens. This qualitative research involved three rounds of co-creation activities with nine experts and nine non-experts to identify major problems and preliminary solutions. As a result, two key issues were addressed from the qualitative data: The problem of area calculation, resolved by simplifying data entry processes, and the issue of material selection within homes, improved by incorporating illustrative images with concise, easily understandable descriptions. The outcome of this research is a framework and wireframe that lays the groundwork for developing user-friendly applications that promote sustainable behaviors in residential energy usage. This research contributes valuable guidelines for developers and stakeholders to create more efficient and user-friendly applications, thus promoting environmental action and sustainable practices in residential settings.
Keywords: Smart Cities and Technologies; Green IT and Sustainability; Innovative Human-Technology Interaction